Extracellular enzymatic activities by Pleurotus species on vegetable wastes - Singh, M P; Srivastava, Abyhishek Kr; Viswakarma, Sanjay Kr; Pandey, Vivek kr; Pandey, Ashwini Kr; Singh, Shailendra Kumar (Mushroom Research, 2015)
Please see the full text